Investigando a formação de professores numa escola integral de ensino fundamental e médio em processo de implantação - Domingues, Gabriela de Campos Vaz (2021)
The purpose of this study is to identify and describe some aspects of continuing training for teachers of a hybrid full-time State school, in implementation in 2020. On this basis, some question motivated and directed the development of this research: What is the continuing education proposal for teachers who work in full-time schools? What are the aims of this proposal? Are these formations faithful to official guidelines? Does the discourse drain into traditional practices that privilege technique, utilitarian instrumentation to apply the curriculum, and detract from the real needs of the school and teachers? The general objective is to analyze how the teacher’s continuing education happens at a hybrid full-time state school in implementation. Specific objectives are: (1) Check how the continuing education proposal for full-time teachers is; (2) Analyze the objectives of this proposal; (3) Identify whether these formations are faithful to official guidelines, or the discourse fades into traditional practices that privilege technique, utilitarian instrumentation for the application of the curriculum and detriment to the real needs of the school and teachers; (4) Study how the formation of a hybrid full-time school occurs; (5) Analyze how it is understood and practiced by the teachers of the school. (6) Analyze how this training is built within the school. The research is qualitative, and it was conducted through documentary analysis (specific legislation and documents produced for the school by the administrative bodies and the school in their daily activities); questionnaire, and online observations of the ATPCG meetings and WhatsApp chat group. Therefore, aspects that constitute continuing education in service is going to be presented in the school context; considering their specificities, their community, faculty, and all those involved, the culture established for personal strengthening and professional development. The research will be based on the following authors: Michael Fullan & Andy Hargreaves (2000) - for the definition of continuing education, professional development of teachers and teaching knowledge; Barroso - concerning the concept of school-centered training; and Viñao Frago - regarding the culture of the managers and the culture of the teachers. Nóvoa (1992); Rui Canário (1998) Christopher Day (1999) Teodoro (2011), Bernard Charlot, and educational documents linked to teacher training and pedagogical practices. The results of this research confirm the hypothesis that the continuing education of teachers of a full school in implementation, ensured by law and organized through Resolutions, is based on legislation, and centralized policies without considering the needs of the school and teachers. Its principles are based on traditional models of ineffective continuing education, whose approach favors the instrumentation of teachers for the application and reproduction of the curriculum, standardizing routines and practices. The school chooses, therefore, for standardized practices and routines in which the teachers end up being, most of the time, receptacles for the absorption and reproduction of the curriculum, a model that has long been the target of criticism, as it opposes the contemporary educational practices that envision the construction of knowledge in a more constructive and autonomous way, this model applied in question on the contrary, perpetuates the already established mold that for the most part does not present the expected educational results.